Bugs, butterflies, beetles & bees - Dowds, Ben Ffrancon; Mills, Andrea; Munsey, Lizzie (Our world in pictures (DK Publishing, Inc.), 2026)
"Uncover the lives of all kinds of bugs -- from moths to mayflies to mantises! Discover a teeming world of voracious leaf munchers, busy pollinators, ruthless parasites, and deadly assasins."--